Theoretical foundations of evaluation of the effectiveness of the state mechanism of response to the threats to the military security - Пелих, А. О. (Аспекти публічного управління, 2015)
In the article the author examines the theoretical foundations of evaluation of the effectiveness of the state mechanism of response to the threats to the military security. Also the author defines the area of the methodological problems of the construction of scorecard of such evaluation.Comparative analysis of the approaches to evaluation of the effectiveness of the state mechanism of response to the threats to the military security, namely economic, social, legal, socially oriented, expert, pragmatic, allowed defining the last one as the most promising. Pragmatic approach is not confined only to distinction of the resulting and economical effectiveness, but also allows defining purposeful effectiveness of the public policy from the point of view of correspondence of its aims to the normative ideals and value standards, which are accepted by the certain society on the certain stage of its de-velopment.The author suggests to distinguish between general and current effectiveness of the functioning of the state mechanism of response to the threats to the military security.General effectiveness is a level of national interests protection in the military sphere. Current effectiveness is determined by the work efficiency of public authorities and bod-ies of state military administration, which consists in the development, adoption and or-ganization of implementation of administrative decisions concerning state response to the threats to the military security.The proposed method for estimating the complex effectiveness provides a more pre-cise tool for evaluation of the public authorities performance in the field of response to the threats to the military security, which greatly increases the practical significance of the results of this assessment.